EVALUASI PELAKSANAAN FOCAL POINT SEBAGAI BENTUK KEBIJAKAN PENGARUSUTAMAAN GENDER DI KOTA SEMARANG - Fadilla Ayu Prasetyo; Ida Hayu Dwimawanti (Journal of Management and Public Policy, 2026)
Gender mainstreaming in Semarang City is measured through various indices, one of which is the Gender Empowerment Index (GEI). One of the local government's efforts to improve the GEI is through the establishment of various PUG institutions at both the regional and local bureaucracy levels, one of which is the Focal Point in each bureaucracy. The existence of the Focal Point aims to advocate for gender mainstreaming, which is reflected in the form of gender data analysis in each bureaucracy. However, despite the various facilities that have been provided and the establishment of these institutions, the GEI data for Semarang City for 2021-2023 shows fluctuating figures that tend to decline. This study aims to analyze the extent of the success of the Focal Point in improving GEI as the most strategic institution at the bureaucracy level in Semarang City, along with its inhibiting factors, using the phenomena of efficiency, effectiveness, adequacy, equity, responsiveness, and accuracy from William N. Dunn, as well as inhibiting factors such as bluffocracy and consultocracy from Christopher Hood and Michael Jackson. A descriptive qualitative approach was used with field observation, documentation, literature study, and in-depth interviews with officials from Office of Women's Empowerment and Child Protection (DP3A), Regional Development Planning Agency (Bappeda), and Tembalang District. Data analysis used the Miles and Hubberman analysis technique through collection, condensation, presentation, and verification through triangulation to assess implementation. The findings show that the Focal Point, which was analyzed in terms of efficiency, adequacy, and accuracy, succeeded in improving Semarang City's GEI in 2024. However, in terms of effectiveness, equity, and responsiveness, it was considered to have contributed less to the improvement of GEI. The inhibiting factors were low substantive understanding and dependence on consultants or external institutions. The researchers recommend strengthening internal capacity, allocating resources appropriately, and conducting continuous monitoring to improve policy responsiveness and accuracy.